Effect of Moderate-Intensity Aerobic Training on Some Hormonal and Metabolic Factors Associated With Breast Cancer in Overweight Postmenopausal Women - Mahnaz Khoramjah; Davood Khorshidi; Mohammad Karimi (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives  Obesity is directly associated with an increased risk of breast cancer in postmenopausal women. The current study aimed to examine the effect of aerobic training at moderate intensity on some biomarkers of breast cancer in overweight postmenopausal women.   Methods & Materials Twenty-four overweight postmenopausal women (Body Mass Index [BMI] Mean±SD =32.01±5.3 kg/m2) with the Mean±SD age of 55.44±4.4 years were randomly divided into the experimental (n=14) and control (n=10) groups. The experimental group received 10 weeks of aerobic training (3 sessions per week at an intensity of 65%-75% of Maximum Heart Rate [MHR]). The controls did not participate in any exercise training. Sex hormone-binding globulin and insulin levels, insulin resistance, body fat percentage, and vo2 max were measured at the beginning and after training. The obtained data were analyzed by analysis of covariance, using SPSS. Results No significant difference was observed in sex hormone-binding globulin, insulin, insulin resistance, and body fat percentage after 10 weeks of aerobic training; however, a significant difference was found in vo2 max between the two groups. Conclusion Short-term moderate-intensity aerobic training appears to have no effects on some biomarkers of breast cancer, such as sex hormone-binding globulin, insulin, and insulin resistance in overweight postmenopausal women. Therefore, further studies are recommended to evaluate the effectiveness of training programs with different intensities and durations.